Penatalaksanaan Fisioterapi Pada Kasus Cerebral Palsy Diplegi Suspect Autism Et Causa Hydrocephalus Di Yayasan Pendidikan Anak Cacat (YPAC) Surakarta - Siti Mardliyah, Qonita; , Totok Budi Santoso, S.Pd., SST. FT., M.P.H (2017)
Background: Cerebral palsy (CP) is an abnormality of or damage to the brain that is non-progressive that occurs in the growth process. In such cases can be performed with physiotherapy modalities. Physiotherapy in this case can control the spasticity and help independence with Neuro Senso (NS) techniques, facilitation, trunk mobilization, and body massage. Objectives: To know the implementation of Physiotherapy in the functional ability, control the spasticity, and prevent contractures, and to help improve the independence of children with Neuro Senso (NS) techniques, facilitation, trunk mobilization, and body massage. Results: After 6 weeks of therapy, the results of the assessment have not been changed. Conclusion: Neuro Senso (NS), facilitation, trunk mobilization, and body massage can improve functional ability, control spasticity, prevent contractures, and to help improve children's independence.